E-cigarette explosions: patient profiles, injury patterns, clinical management, and outcome - Alexander Kaltenborn; Khaled Dastagir; Alperen S. Bingoel; Peter M. Vogt; Nicco Krezdorn (JPRAS Open, 2023)
Background: E-cigarette abuse, also known as vaping, is a widespread habit. Recently, there have been increasing reports of explosions of these devices resulting in serious burn injuries, especially to the groin, hand, and face. Overheating rechargeable lithium-ion batteries are supposed to be the responsible mechanism, especially in low quality fabrications. Methods: In this single-center retrospective study, data of 46 patients are presented and analyzed. In addition to information on demographics, injury patterns, and treatment options, this is the first study investigating outcome after an average of 13 months via a standardized telephone interview of 31 patients (67%). Patients were specifically asked regarding their outcome, vaping habits, technical modifications to their devices and supply source. Results: Patients were mainly male (98.2%) with a median age of 36 years. Typical injury patterns included the groin region (n = 32; 69%), hands (n = 12; 25%) and face (n = 3; 7%). All patients underwent debridement, in nine cases hydrotherapeutically. 61% (n = 28) underwent consecutive tangential necrectomy and subsequent split thickness skin graft transplantation. Wound infection was observed in 18 patients (39%), with burn depth as a significant risk factor (p < 0.001). 91% of the followed-up patients were satisfied. Surprisingly, 38% were still using e-cigarettes. 42% (n = 13) reported manual modifications of their devices to prolong battery life or increasing smoke production. Conclusions: Injuries from exploding e-cigarettes can be serious and should be treated in a specialized burn center. E-cigarette explosions lead to characteristic injury patterns and often need surgical treatment. This should be made more public to reduce their use and keep people from modifying the devices. The counterintuitive and irrational observation of a high rate of abuse even after the injury underlines their addiction potential.